The role of attachment to the foster parent with regard to suicidal risk among adult survivors of childhood maltreatment. (June 2022) - Danner Touati, Camille; Miljkovitch, Raphaële; Sirparanta, Aino; Deborde, Anne-Sohpie
Abstract: Background: Childhood maltreatment is associated with an increased risk of insecure/disorganized attachment and in turn with suicidal risk (SR). Out-of-family placement is aimed at interrupting child exposure to further abuse and at providing the necessary security for proper development via the establishment of an alternative attachment relationship. However, the actual protective role of this type of care is not clear given the high rates of SR among institutionalized or foster children. Objective: The aim of this study was to examine whether 1) attachment to the biological parents mediates the association between abuse and SR and 2) attachment to a foster parent (whether from a foster home or an institution) moderates the effect of attachment to biological parents on SR. Participants: The sample consisted of 77 adults (52 female; 25 male; mean age: 26.6 years) who received out-of-home care during childhood. Method: The Childhood Trauma Questionnaire and the Mini International Neuropsychiatric Interview (for SR) were used. The Attachment Multiple Model Interview was also administered to assess attachment to each biological parent and to the foster parent. Results: Results show that attachment (security and disorganization) to the biological mother mediates the link between abuse and SR and that attachment to the foster parent moderates the link between attachment to the biological mother and SR. Conclusions: : Findings point to the importance of interventions aimed at supporting the establishment of a secure attachment relationship between children in care and their foster parents.